Tinjauan Yuridis Pedoman Hakim Dalam Mengadili Perempuan Berhadapan Dengan Hukum Di Indonesia - Suri, Rahmah Atika; Zulfa, Eva Achjadi (Universitas Sang Bumi Ruwa Jurai, 2025)
This research discusses the importance of legal protection for women in conflict with the law, particularly those who are victims of sexual violence, by highlighting the role of judges as key actors in ensuring justice that sides with the victims. The main focus of this study is an analysis of the provisions in Supreme Court Regulation (PERMA) Number 3 of 2017 on Guidelines for Adjudicating Cases Involving Women in Conflict with the Law and Law Number 12 of 2022 on the Crime of Sexual Violence (UU TPKS). Both serve as important instruments in shaping a fair and gender-sensitive legal perspective. This research employs a doctrinal legal method, which involves a literature-based approach and normative analysis of relevant legislation. The author examines the legal substance and principles of gender-based justice that must be applied in court proceedings, including the principles of non-discrimination, respect for women's dignity, and legal protection that is responsive to victims. The findings indicate that the synergy between PERMA and the Sexual Violence Crime Law represents a strategic step in creating an inclusive criminal justice system, ensuring the rights of victims, and strengthening judicial accountability in upholding substantive justice. Therefore, the development and implementation of gender-responsive law become a crucial foundation for realizing true justice for women victims of sexual violence in Indonesia.